2016
DOI: 10.1027/1192-5604/a000077
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Neurological Priming on the Rorschach

Abstract: Abstract. This article introduces a new scientific paradigm that might allow the investigation of the neurological correlates of the Rorschach test without using expensive and time consuming tools such as the fMRI or the EEG. Based on the literature on the Mozart effect, we anticipated that preactivation of a given brain network before exposure to the Rorschach cards would associate with the increased production of responses (or determinants) presumed to be associated with that same network. To pilot test this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…With regard to the determinants associated with movement, Rausch de Traubenberg (1998) stresses that responses with great movement (K) may be understood as elements of regulation and control that reflect the ego's role, in addition to evoking indicators of the ability to internalize, and the possession of intelligence, creativity, imagination. Recent studies describe the biological foundation of the human movement response and shows that it is related to the effective use of the mentalization function (Ando et al, 2015;Giromini et al, 2016;Giromini, Porcelli, Viglione, Parolin, & Pineda, 2010). Grønnerød (2003) discussed that variables related to state-like features of personality in CS were associated with lower stability levels; in his study, for example, state features were defined as the influence of the m (inanimate movement) and Y (shadding) scores and provided indications that state-like features have a negative effect on stability.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the determinants associated with movement, Rausch de Traubenberg (1998) stresses that responses with great movement (K) may be understood as elements of regulation and control that reflect the ego's role, in addition to evoking indicators of the ability to internalize, and the possession of intelligence, creativity, imagination. Recent studies describe the biological foundation of the human movement response and shows that it is related to the effective use of the mentalization function (Ando et al, 2015;Giromini et al, 2016;Giromini, Porcelli, Viglione, Parolin, & Pineda, 2010). Grønnerød (2003) discussed that variables related to state-like features of personality in CS were associated with lower stability levels; in his study, for example, state features were defined as the influence of the m (inanimate movement) and Y (shadding) scores and provided indications that state-like features have a negative effect on stability.…”
Section: Discussionmentioning
confidence: 99%
“…Other Rorschach determinants (i.e., form, color, and shading) may reflect distinct perceptual features recognized directly from the actual characteristics of the inkblots, while human movement responses (or M responses) are added to the stimulus field, presumably as a result of imagined activity (Exner, 2003). Several studies support the validity of the M responses as linked to an identification mechanism (e.g., Meyer et al, 2002;Viglione et al, 2012;Mihura et al, 2012;Giromini et al, 2016). The inter-rater reliability of the M response also is excellent (Cicchetti, 1994), indicating that two independent raters, blind to each other's evaluation, code for the presence or absence of M responses reliably, with intraclass correlation coefficients (ICC) ranging from 0.96 to 0.97 (Meyer et al, 2002;Mihura et al, 2012;Pignolo et al, 2017;Viglione and Taylor, 2003;Viglione et al, 2012).…”
Section: Mu Suppression Ambiguous Rorschach Stimuli and Movement Atmentioning
confidence: 94%
“…Rapaport (1950) explained that the test expresses the unconscious organizing principles of personality, which are seen as dynamic processes rather than the contents of a person's inner life. Given the static nature of the Rorschach stimuli, the perceived movement in a response is due to an interaction between the features of the blot and the inner world of the subject (Piotrowski, 1977;Porcelli & Kleiger, 2016;Rapaport et al, 1949;Rorschach, 1921), which often involves identification mechanisms (Giromini et al, 2016;Klopfer & Kelley, 1942;Piotrowski, 1957). Klopfer and Davidson (1962) suggested that movement perception reflects the subject's attitudes toward fantasies, instinctive drives, and unconscious conflicts.…”
Section: Rorschach: Unconscious and Implicit Elementsmentioning
confidence: 99%